On the Trigger of V-to-T - Castillo Orihuela Concha (Miscelánea: A Journal of English and American Studies, 2014)
This paper deals with the trigger of V-to-T movement and claims that rich morphology is the actual cause of verb-raising as occurring in core or narrow syntax. After rejecting a gross analysis of φ–features and/or τ–features as the cause of V-to-T, it is argued that the trigger of V-to-T lies in a stem-feature that T must value, which corresponds morphologically with the so-called thematic or stem vowel, and which is responsible for the availability (in V-moving languages) of productive stem verb classes. The relevant productivity lies in the systematic co-variation of φ–features and/or τ–features throughout the verbal paradigms of corresponding languages. The account proposed of the computation of T´s features in core or narrow syntax (among which is the cited T´s stem-feature) is based originally on Pesetsky and Torrego´s (2004b/2007) idea that T´s features can be interpretable though unvalued on T itself. The last Sections of the paper focus on the loss of V-to-T in the Germanic family of languages, which correlates with the demise in their productive stem verb classes. In the specific case of English, it is argued that the process of development of the new auxiliary do, which in turn depends on the reanalysis of modals, is responsible for the time-gap existing between the loss of T´s stem-feature and the loss of V-to-T in the language.